2016
DOI: 10.3346/jkms.2016.31.10.1641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brace to Osteoporotic Vertebral Fracture: a Meta-Analysis

Abstract: Brace is one of the most commonly used interventions to manage osteoporotic vertebral fracture. However, its authentic effectiveness remains unclear. The aim of this study was to investigate the efficacy of brace in patients with osteoporotic vertebral fractures. We conducted a literature review and meta-analysis following the guideline and handbook of the Cochrane collaboration. Ten published articles were included in this study and data from 4 randomized controlled trials were analyzed. Low quality evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 19 publications
1
33
0
5
Order By: Relevance
“…In a meta-analysis, the effect of treatment of orthoses has been investigated on back pain and the kyphosis angle in rehabilitation after an acute or sub-acute vertebral fracture. The results showed that treatment with the activating spinal orthosis after a sub-acute vertebral fracture significantly improved back pain and the kyphosis angle but the overall quality of the results was rated as low [ 39 ]. This may indicate that the kyphosis angle may be affected in a sub-acute stage, but it will be more difficult at a later stage.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, the effect of treatment of orthoses has been investigated on back pain and the kyphosis angle in rehabilitation after an acute or sub-acute vertebral fracture. The results showed that treatment with the activating spinal orthosis after a sub-acute vertebral fracture significantly improved back pain and the kyphosis angle but the overall quality of the results was rated as low [ 39 ]. This may indicate that the kyphosis angle may be affected in a sub-acute stage, but it will be more difficult at a later stage.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this has led to previous meta-analyses, in the general rather than elderly population, of equivocal nature without clear recommendations concerning their use. 37,38,40 It has been previously posited that immobilization with orthoses leads to muscle atrophy and is therefore paradoxically detrimental to vertebral healing and posture. Indeed, one survey demonstrated that a similar belief was held by up to 50% of clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The start of non-surgical treatment for stable OSF usually consists of initial bed rest, analgesia, early physiotherapy, early rehabilitation, and a rigid spinal brace (orthosis). Pain related to the OSF may last up to 4 months [ 16 ]. Spinal braces are usually applied for a minimum of 3 weeks and up to 12 months, depending on the patient’s symptoms and the fracture healing progress [ 17 , 18 , 19 , 20 ].…”
Section: Passive Spine Braces In the Treatment Of Osteoporotic Spimentioning
confidence: 99%
“…A recent meta-analysis looking at the effect of a brace on OSF concluded that a Spino-med orthosis, which work with a concept of improving the strength of users’ trunk muscle, unlike traditional rigid braces which offer immobilization of the spine, may subsequently reduce pain, reduce kyphosis angle deterioration, and improve quality of life [ 16 ]. However, due to the high risk of bias in the blinding process and outcome assessment in the included studies, only low-quality evidence proved using Spino-med braces could bring large and significant beneficial effect to patients with subacute osteoporotic vertebral fractures [ 18 ].…”
Section: Passive Spine Braces In the Treatment Of Osteoporotic Spimentioning
confidence: 99%